(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The system which involves in character identification of Brahmi letters from epigraphy and converts to current Tamil character format.Identification of earliest Tamil characters is one of the hardest part. If the letters are on the walls, it is still more difficulty in recognizing the characters. Character recognition has reached near perfection in English and other language text. Identification of epigraphy brahmi characters is very difficult because brahmi characters has been used from 3rd Century BCE to 4th Century CE. The accuracy level is not high in Brahmi letters because of these reasons- First the consonants are similar to consonantal vowel characters, second the author doesn’t inscribe the Brahmi letterings correctly and the fonts are inscribed in various styles and strokes. Only few people are known with ancient character if this remains, all the valuable data given by our forefather will not be identified by the future generation. In this survey paper, we describe and compare many techniques of identification through table.